Empowerment of elderly groups through the elderly health services assistance program - Lufthiani; Karota, Evi; Sitepu, Nunung F (Talenta Publisher, 2019)
Health problems in the elderly begins with the process of deterioration of body cells, which causes a decrease in function and immune system so that it can increase risk factors for disease. Some diseases that are often experienced by the elderly include, hypertension, diabetes mellitus, rheumatism, gout, hearing loss, vision problems, osteoporosis, and others. These conditions will have an impact on increasing morbidity and mortality, declining quality of life, and increasing health financing. The method of implementing community service activities is carried out by educating health issues, providing guidance, counseling and mentoring to 20 elderly groups. The purpose of community service activities is to increase health care efforts which are expected to implement programs to create or improve the ability to live healthy in the community both individuals and groups to be able to solve various problems related to health improvement and disease prevention on an ongoing basis. Education is carried out with health education about general elderly diseases that often occur, namely Diabetes and Gout, then conduct guidance and counseling by dividing into groups, and provide assistance by teaching foot exercises and foot care. Results The implementation of community service activities shows the results that Good Knowledge about degenerative diseases (85.0%), after the mentoring activities namely guidance, counseling, foot gymnastics simulation and foot care. Paired t-test results before and after the assistance was given p value of 0.007. It is expected that the elderly group can be independent in efforts to prevent degenerative diseases that are focused on diabetes mellitus